2021
DOI: 10.3390/polym13183045
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides as Stabilizers for Polymeric Microcarriers Fabrication

Abstract: Biodegradable polymeric microparticles are widely used in drug delivery systems with prolonged-release profiles and/or cell microcarriers. Their fabrication via the oil/water emulsion solvent evaporation technique has normally required emulsifiers in the aqueous phase. The present work aims to evaluate the effectiveness of various polysaccharides, such as chitosan, hyaluronic acid, cellulose, arabinogalactan, guar and their derivatives, as an alternative to synthetic surfactants for polylactide microparticle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To solve these issues, pickering particles or a mix of surfactants and gelling agents (to stabilize the inner or outer emulsion or gel the water phase or crystallize the fat phase) may be used [5]. Therefore, most recent research has focused on formulating double emulsions stabilized by biopolymers [6], such as milk protein concentrate [7], sodium caseinate [8], peanut protein isolate, rice bran protein isolate, soybean protein isolate, whey protein isolate [9], sodium caseinate and k-carrageenan [10], alginate [11], chitosan, cellulose, arabinogalactan, guar and their derivatives [12], calcium alginate [13] and xanthan gum [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…To solve these issues, pickering particles or a mix of surfactants and gelling agents (to stabilize the inner or outer emulsion or gel the water phase or crystallize the fat phase) may be used [5]. Therefore, most recent research has focused on formulating double emulsions stabilized by biopolymers [6], such as milk protein concentrate [7], sodium caseinate [8], peanut protein isolate, rice bran protein isolate, soybean protein isolate, whey protein isolate [9], sodium caseinate and k-carrageenan [10], alginate [11], chitosan, cellulose, arabinogalactan, guar and their derivatives [12], calcium alginate [13] and xanthan gum [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the synthesis of HPS-DDS, such as nanoparticles (NPs) [25,26], micelles [27], liposomes [28], microemulsions [29], hydrogels [30], and microneedles [31], for the treatment of various diseases. These studies show that HPS can serve as drug carriers [32], stabilizers [33], solubilizers [34], and emulsifiers [35]. Considering their bioactivity, these HPS can also act as adjuvants [36], immunomodulators [37], and bioactive macromolecular drugs [38] that exert synergistic effects or amplify the therapeutic activities of primary drugs.…”
Section: Introductionmentioning
confidence: 98%
“…This approach relies on the stabilization of the oil/water interface by nHA dispersed within the aqueous phase, while the oil one consists of polyester solution. Solid nanoparticles of various nature could stabilize the emulsion interface even more effectively than molecular surfactants [ 31 , 32 , 33 ]. It allows to avoid the usage of additional emulsifiers and to fabricate nHA-armored polyester core/shell microparticles.…”
Section: Introductionmentioning
confidence: 99%